REFLEKSI FITNAH PEDOFILIA TERHADAP RASULULLAH SAW (STUDI ANALISIS MATAN HADIS DAN LITERATUR ISLAM) - Riyadhotul Ilmi (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
This study examines the accusation of pedophilia against Prophet Muhammad SAW which spreads widely in the digital era through orientalist and missionary narratives. The aims of this study are first,  to map and analyze the narrative of pedophilia accusation along with orientalist and missionary arguments; second, to analyze the matan (text) of the core hadiths concerning the Prophet's marriage to Aisha RA; and third, to describe the perspective of Islamic literature and the arguments of modern Muslim scholars in refuting the accusation. This research is a library research using a descriptive-analytical qualitative approach. Primary data sources include the major hadith collections (Kutub al-Tis‘ah), Qur’anic exegesis books (Tafsir Ibn Kathir and Tafsir Al-Mishbah), and jurisprudence books from the Hanafi and Shafi‘i schools. The findings indicate that the pedophilia accusation is scientifically unfounded because it is based on anachronis imposing 21st-century moral standards onto 7th. Mat an analysis confirms that the hadiths concerning the Prophet's marriage to Aisha RA clearly distinguish between the marriage contract and its consummation. Islamic literature encompassing Exegesis, Hadith, Jurisprudence, and Maqasid al-Shariah consistently rejects this accusation, and modern Muslim scholars have provided comprehensive refutations.